2014
DOI: 10.1371/journal.ppat.1003947
|View full text |Cite
|
Sign up to set email alerts
|

Gambiense Human African Trypanosomiasis and Immunological Memory: Effect on Phenotypic Lymphocyte Profiles and Humoral Immunity

Abstract: In mice, experimental infection with Trypanosoma brucei causes decreased bone marrow B-cell development, abolished splenic B-cell maturation and loss of antibody mediated protection including vaccine induced memory responses. Nothing is known about this phenomenon in human African trypanosomiasis (HAT), but if occurring, it would imply the need of revaccination of HAT patients after therapy and abolish hope for a HAT vaccine. The effect of gambiense HAT on peripheral blood memory T- and B-cells and on innate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…b . gambiense show a significant increase in T cell-independent B cells and a significant decrease in T cell-dependent B cells as a percentage of total blood lymphocytes accompanied by a significant decrease in anti-measles antibody in serum relative to age-, gender- and habitat-matched uninfected individuals, although not of a level to compromise immunity [ 28 ]. It remains possible that there is a link between the infection-induced mechanism that causes the depletion of splenic B2 B cells in trypanosome-infected mice, and those that prevent the development of trypanosome-specific IgG antibodies in infected cattle [ 29 ] and cause the proportional decrease in T cell-dependent relative to T cell-independent B cells in the peripheral blood of T .…”
Section: Introductionmentioning
confidence: 99%
“…b . gambiense show a significant increase in T cell-independent B cells and a significant decrease in T cell-dependent B cells as a percentage of total blood lymphocytes accompanied by a significant decrease in anti-measles antibody in serum relative to age-, gender- and habitat-matched uninfected individuals, although not of a level to compromise immunity [ 28 ]. It remains possible that there is a link between the infection-induced mechanism that causes the depletion of splenic B2 B cells in trypanosome-infected mice, and those that prevent the development of trypanosome-specific IgG antibodies in infected cattle [ 29 ] and cause the proportional decrease in T cell-dependent relative to T cell-independent B cells in the peripheral blood of T .…”
Section: Introductionmentioning
confidence: 99%
“…African sleeping sickness is a vector borne disease of mammals, caused by Trypanosoma brucei ( T. brucei ), for which the development of more effective, safe, and affordable chemotherapies remains a major goal. Vaccines are unlikely to be suitable [1] [3] , and therefore disease control relies exclusively on chemotherapy. The glucose-based metabolism is a key metabolic pathway for bloodstream forms, the mammalian infective stages.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Lejon et al . recently reported a reduction in memory B cells in HAT patients, although after curative treatment, antimeasles antibodies recovered to a critical threshold level. However, the protective capacity of the recovered response could not be assessed, and the authors suggested themselves that it would be crucial to assess antibody functionality in the future.…”
Section: Discussionmentioning
confidence: 95%